Trump-Kim summit – S. Rajaratnam and Singapore’s role - Chong, Alan (2018)
Hosting the Trump-Kim Summit is entirely consistent with the vision of Singapore’s first foreign minister – S. Rajaratnam. Yet, it is not enough that Singapore is trusted and neutral. Singapore must have the capacity and capability to actually host an unprecedented summit that enjoys the confidence of the President of the United States of America and the Leader of the Democratic People’s Republic of Korea, who are officially each other’s worst enemies.